Early Inititation of Breastfeeding (EIBF) and Exclusive Breastfeeding in Districts/Cities - Sulistyowati, Indah; Cahyati, Widya Hary (Universitas Negeri Semarang, 2025)
WHO recommends Early Initiation of Breastfeeding (EIBF) during the first hour of life, maintaining exclusive breastfeeding for up to 6 months postpartum, and continuing breastfeeding after this period in addition to healthy foods suitable for infants up to 2 years of age or more. This form of feeding is considered effective in ensuring the health and survival of newborns worldwide. Early Initiation of Breastfeeding (EIBF) will also greatly assist in the sustainability of exclusive breastfeeding (breast milk only) and the duration of breastfeeding. The percentage of newborns who received EIBF in Central Java Province in 2023 was 87.7%, an increase compared to the achievement in 2022 of 85.9%. Meanwhile, the percentage of exclusive breastfeeding for infants aged 0-6 months in Central Java in 2023 was 64.3%, decreasing when compared to the percentage of exclusive breastfeeding in 2022, which was 71.4%. The purpose of the study was to answer the relationship between Early Initiation of Breastfeeding (EIBF) and Exclusive Breastfeeding. The analysis involved Early Initiation of Breastfeeding (EIBF) as an independent variable, and Exclusive Breastfeeding as a dependent variable. The relationship analysis was carried out using a scatter plot diagram. There are 5 regencies or cities that have exclusive breastfeeding coverage above the target of 80%, namely Klaten Regency, Jepara Regency, Purworejo Regency, Semarang City and Rembang Regency. Meanwhile, the lowest exclusive breastfeeding coverage was achieved by Semarang Regency (25.54%), with EIBF coverage (94.82%). There is a linear and positive relationship between Early Initiation of Breastfeeding (EIBF) and exclusive breastfeeding. It is necessary to examine other variables that contribute to exclusive breastfeeding to increase the coverage of exclusive breastfeeding in regencies or cities that have not met the target.